Meningkatkan Perkembangan Bahasa Anak Usia Dini melalui Metode Tanya Jawab di RA Baiturrahim Jakarta Pusat - Solihin, Ahmad; Maesaroh, Asih (Prodi PIAUD Fakultas Tarbiyah Insitut PTIQ Jakarta, 2024)
Early childhood language development according to nativist theory states that early childhood children have natural or innate language abilities. So they can compose various kinds of sentences without practice, reinforcement, or imitating adult language. However, in this case the researchers saw that not all children had the same language skills because they were motivated by several different factors. Researchers try to conduct research by improving early childhood language development through the question and answer method. Language development is an important aspect for young children in preparing and maturing themselves in preparation for further education. Language development can be useful for older children and for communicating with the wider community. This research was motivated by the lack of children receiving stimulation in language development. The research was carried out using Class Action Assessment using direct observation and documentation data collection techniques in the classroom while the action was taking place. This research was conducted on children aged 5-6 years who were in group B for the 2021/2022 school year. The use of this method was successful in increasing language development in the ability to: 1) answer more complex questions 2) compose simple sentences with complete structures 3) have more words to express ideas to other people. This question and answer method can stimulate children to express language confidently.